Double charged surface layers in lead halide perovskite crystals - Goriely, A; Sarmah, S; Burlakov, V; Yengel, E; Murali, B; Alarousu, E; El-Zohry, A; Yang, C; Alias, M; Zhumekenov, A; Saidaminov, M; Chao, N; et al. (American Chemical Society, 2017)
Understanding defect chemistry, particularly ion migration, and its significant effect on the surface’s optical and electronic properties is one of the major challenges impeding the development of hybrid perovskite-based devices. Here, using both experimental and theoretical approaches, we demonstrate that the surface layers of the perovskite crystals may acquire a high concentration of positively charged halide vacancies with the complementary negatively charged halide ions pushed to the surface. This charge separation near to the surface generate an electric field that can induce a shift in the optical band gap of the surface layers to higher energy compared to the bulk counterpart. We found that the charge separation, electric field and the amplitude of shift in the bandgap strongly depend on the halides and organic moieties of perovskites crystals. Our findings reveal the peculiarity of surface effects that is currently limiting the application of perovskite crystals and more importantly explain their origins, thus enabling viable surface passivation strategies to remediate them.